Gastric Intramural Hematoma: A Case Report and Literature Review - Vivek Dhawan; Ahmed Mohamed; Richard N Fedorak (Canadian Journal of Gastroenterology)
Intramural hematoma of the gastrointestinal tract is an uncommon occurrence, with the majority being localized to the esophagus or duodenum. Hematoma of the gastric wall is very rare, and has been described most commonly in association with coagulopathy, peptic ulcer disease, trauma, and amyloid-associated microaneurysms. A case of massive gastric intramural hematoma, secondary to anticoagulation therapy, and a gastric ulcer that was successfully managed with conservative therapy, is presented. A literature review of previously reported cases of gastric hematoma is also provided.